Bothrops jararaca Snake Venom Inflammation Induced in Human Whole Blood: Role of the Complement System - Leonel, Thyago Bispo; Gabrili, Joel José Megale; Squaiella-Baptistão, Carla Cristina; Woodruff, Trent M.; Lambris, John D.; Tambourgi, Denise V. (Frontiers in Immunology, 2022)
The clinical manifestations of envenomation by Bothrops species are complex and characterized by prominent local effects that can progress to tissue loss, physical disability, or amputation. Systemic signs can also occur, such as hemorrhage, coagulopathy, shock, and acute kidney failure. The rapid development of local clinical manifestations is accompanied by the presence of mediators of the inflammatory process originating from tissues damaged by the bothropic venom. Considering the important role that the complement system plays in the inflammatory response, in this study, we analyzed the action of Bothrops jararaca snake venom on the complement system and cell surface receptors involved in innate immunity using an ex vivo human whole blood model. B. jararaca venom was able to induce activation of the complement system in the human whole blood model and promoted a significant increase in the production of anaphylatoxins C3a/C3a-desArg, C4a/C4a-desArg, C5a/C5a-desArg and sTCC. In leukocytes, the venom of B. jararaca reduced the expression of CD11b, CD14 and C5aR1. Inhibition of the C3 component by Cp40, an inhibitor of C3, resulted in a reduction of C3a/C3a-desArg, C5a/C5a-desArg and sTCC to basal levels in samples stimulated with the venom. Exposure to B. jararaca venom induced the production of inflammatory cytokines and chemokines such as TNF-α, IL-8/CXCL8, MCP-1/CCL2 and MIG/CXCL9 in the human whole blood model. Treatment with Cp40 promoted a significant reduction in the production of TNF-α, IL-8/CXCL8 and MCP-1/CCL2. C5aR1 inhibition with PMX205 also promoted a reduction of TNF-α and IL-8/CXCL8 to basal levels in the samples stimulated with venom. In conclusion, the data presented here suggest that the activation of the complement system promoted by the venom of the snake B. jararaca in the human whole blood model significantly contributes to the inflammatory process. The control of several inflammatory parameters using Cp40, an inhibitor of the C3 component, and PMX205, a C5aR1 antagonist, indicates that complement inhibition may represent a potential therapeutic tool in B. jararaca envenoming.